Ideology and Islamization in Malaysia: an analysis using a sociology Of knowledge - Azizan Had; Romzi Ationg (2020)
The past thirty years have seen a swift advance in the idea of Islamization of Knowledge (IoK) in Malaysia. The term ‘Islamization’ meaning the reform of knowledge in Islam, has been used by Syed Muhammad Naquib al-Attas and Ismail Al-Faruqi, especially in the late 1970s, to explicate the process of Islamizing and the reformation of academia in the Muslim world, in the aftermath of the ‘malaise’ of the ʿummah. The IoK project in Malaysia is substantially related to the Sociology of Knowledge (SoK) theory which accentuates that ideas are closely related to the settings where the ideas initiated. This paper analyses the origin of the IoK as an ideology using a SoK theory proposed by Karl Mannheim (1893-1947). According to Mannheim, the particular conception of ideology implied when a person is being skeptics of the ideas forwarded by his opponent whether it is an individual, groups or organization. From this point of view, we are looking at the person’s idea merely as a disguise or falsification of his true nature or interest. Mannheim called this a ‘distortion’ rather than simply lies and it can gradually become clear when it is contrasted with the total conception of ideology (Mannheim, 1954). The total conception of ideology for Mannheim is somewhat different in its scope where it deals with the ideology of a certain time in history or a historical-social group and it is concerned with the characteristics and composition of the total structure of the mind of the people or group in this certain time frame (Mannheim, 1954). Furthermore, the paper investigates a different perspective of knowledge where it will look into the questions of ‘What makes Malaysia's intellectual and political environment so conducive to generating the IoK project? What were the main reasons for the government to engage in a project like IoK? What was the role of the Prime Minister of Malaysia, Mahathir Mohammad in promoting IoK and what was the reason for him in doing so?’ The paper concludes that Mahathir’s Islamization project is also part of his bid to stay in power by controlling knowledge. Under Mahathir’s rule, he tries to control the way knowledge is disseminated to the people by controlling Islamic institutions, strengthen Islamic law against the civil law of the country and formed Islamic based institution of higher learning promoting his way of Islam.